Jurnalisme Politik: Keberpihakan Media claim Pemilu 2004 - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The idea of independent political journalism failed to perform during the 2004 general election in Indonesia. Instead of keeping equal distance from the bourgeois dan capitalist interest, a number of the journalists even proud to be able to serve them.